2017
DOI: 10.1371/journal.pone.0177110
|View full text |Cite
|
Sign up to set email alerts
|

HNF1α defect influences post-prandial lipid regulation

Abstract: PurposeHepatocyte nuclear factor 1 alpha (HNF1α) defects cause Mature Onset Diabetes of the Young type 3 (MODY3), characterized by defects in beta-cell insulin secretion. However, HNF1α is involved in many other metabolic pathways with relevance for monogenic or polygenic type 2 diabetes. We aimed to investigate gut hormones, lipids, and insulin regulation in response to a meal test in HNF1α defect carriers (MODY3) compared to non-diabetic subjects (controls) and type 2 diabetes (T2D).MethodsWe administered a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
5
0
2
Order By: Relevance
“…insulin level and lipometabolic disorders might be related to targeted tissues of insulin, i.e., liver and surrounding adipose. Deficiency of HNF1α in liver lipometabolism may lead to diabetes and hypercholesterolemia by increasing bile acid and cholesterol synthesis [20]. The cross-talking of insulin levels and AMPKα/HNF1α supports AMPK-mTOR-HNF1α…”
Section: Data Availabilitymentioning
confidence: 98%
“…insulin level and lipometabolic disorders might be related to targeted tissues of insulin, i.e., liver and surrounding adipose. Deficiency of HNF1α in liver lipometabolism may lead to diabetes and hypercholesterolemia by increasing bile acid and cholesterol synthesis [20]. The cross-talking of insulin levels and AMPKα/HNF1α supports AMPK-mTOR-HNF1α…”
Section: Data Availabilitymentioning
confidence: 98%
“…HNF1α and CTRP6 are supposed to be the substance metabolic indicators of these two targets during lowering lipid (32, 33). Deficiency of HNF1α in liver lipometabolism may lead to diabetes and hypercholesterolemia by increasing bile acid and cholesterol synthesis (34, 35). The cross-talking of insulin level and AMPKα/HNF1α supports AMPK-mTOR-HNF1α pathway for the treatment of lipometabolism and insulin dysfunction (36).…”
Section: Discussionmentioning
confidence: 99%
“…LPL encodes lipoprotein lipase, which is mostly found in the endothelial surfaces of capillaries in organs such as adipose tissues, liver, and skeletal muscle, where it hydrolyzes triglyceride-rich lipoprotein, including VLDL and chylomicrons [20]. This is why a previous study demonstrated that triglyceride levels were lower in MODY3 than in T2D [21]. Lipid levels in MODY3 patients were found to be no different from those in T1D patients in our study and in a previous study by Fendler et al [22]; this may be explained by small sample sizes.…”
Section: Discussionmentioning
confidence: 99%